Visual and opto-electronic autocollimator - Fesenko, A. V.; Borovitskii, V. N. (Technology and design in electronic equipment, 2012)
The article presents advantages of optical-electronic autocollimator to the visual ones. The possibility is shown to upgrade existing visual systems by replacing the autocollimating eyepieces by the units containing multielement detectors and connecting them to the computer. The brief characteristics of autocollimating eyepieces and modern optoelectronic autocollimators are given.